Impact of socio-demographic factors, lifestyle and health status on nutritional status among the elderly in Taiwan - Poda, Ghislain G. (Nutr Res Pract, 2019)
BACKGROUND/OBJECTIVES: Aging is an imperative problem for many countries in this century, and presents several challenges for the maintenance of good nutritional status. This study aims to assess the impact of socio-demographic factors, lifestyle and health status on the nutritional status among the elderly in Taiwan. SUBJECTS/METHODS: A cross-sectional study was carried out in Taiwan. Data were obtained from the Mei Jau Health Management Institution, which is a private health evaluation provider with multiple health screening centers in Taiwan and Asia. This study included 7947 adults aged 65 years or above. The data were extracted between 2001 to 2010. Nutritional status was assessed using anthropometric data, biochemical data and dietary intake information. RESULTS: Among the 7947 participants with mean age of 70.1 (SD = 4.5) years, 20.2%, 6.6%, 10.5% and 52.5% experienced underweight, protein malnutrition, anemia and inadequate dietary intake in the past month, respectively. Age was negatively correlated with body weight (r = −0.19, P = 0.02), body mass index (r = −0.41, P < 0.001), albumin level (r = −0.93, P < 0.001) and hemoglobin level (r = −0.30, P = 0.008). Age above 70 years, gender, unmarried status, retirement, lack of education, low family income, smoking, alcohol drinking, sleep duration of 6-8 hours, vegetarian diet, multiple medications, comorbidity and dysphagia were positively associated with malnutrition in older adults. CONCLUSIONS: Underweight and inadequate dietary intake are prevalent among the elderly in Taiwan. Vegetarian diet, multiple medications, comorbidity, dysphagia and lifestyle factors such as smoking, alcohol drinking and sleep duration of 6–8 hours are risk factors for undernutrition in older adults.